NTA CSIR UGC NET SET Life Sciences : JRF and Lecturership - Ashish Nagesh; Kumar, Prashant Hossain, Quisher J (New Delhi Arihant Publications, 2025)
UNIT I: Basic Physical and Chemical Concepts in Biology, Bioenergetics and Catalysis, Organization and Metabolism of Biomolecules, UNIT II: The Cell: Structure and Function, Structure of Chromosome and Cell Cycle, UNIT II: DNA Replication, Repair and Recombination, RNA Synthesis and Processing, Protein Synthesis and Processing, Control of Gene Expression, UNIT IV: Host Parasite Interactions, Cell Signaling and Cellular Communication, Cancer, UNIT V: Immune System, Concepts and Early Development in Plants and Animals, UNIT VI: Morphogenesis and Organogenesis in Plants and Animals, Physiological Metabolism in Plants, Growth Hormone and Photobiology, UNIT VII: Solute Transport and Stress Physiology, Digestion and Respiratory System, Blood Vascular System, Excretory System and Thermoregulation, Neuroendocrine System and Reproduction, UNIT VIII: Mendelis and its Extensions, Gene Mapping, Extrachromosomal Inheritance and Microbial Genetics, Human and Quantitative Genetics, Genetic Variation, UNIT XI: Classification of Livings, Indian Sub-Continent and its Organisms, UNIT X: The Environment and Population, Community Dynamics, Ecosystem Physiology, Pollution and Biodiversity Conservation, UNIT XI: Origin of Life and Evolutionary Thoughts, Evolution: Methods of Studying and Mechanisms, Behaviour and Evolution, UNIT XII: Applied Biology, UNIT XIII: Molecular Biology and Recombinant DNA Methods, Histochemical and Immunotechniques, Biophysical Methods, Statistical Methods, Radiolabeling Techniques, Microscopic Techniques, Electrophysiological Methods, Methods in Field Biology, Computational Methods, Sample Questions Provided on CSIR Website, Solved Paper 2024
Keywords: Life Siences